Differential temperature responses between Plutella xylostella and its specialist endo‐larval parasitoid Diadegma semiclausum—Implications for biological control. (11th October 2021) - Wang, Leyun; Etebari, Kayvan; Zhao, Zihua; Walter, Gimme H.; Furlong, Michael J.
Abstract: Understanding the thermal dynamics of host–parasitoid interactions is crucial to predicting how biological control of pest insects by parasitoids might be affected by geographic location and climate change. We compared performance traits of Plutella xylostella (Lepidoptera: Plutellidae) and its solitary endo‐larval parasitoid Diadegma semiclausum (Hymenoptera: Ichneumonidae), over a wide range of constant rearing temperatures (10–30°C). Parasitoids reared at 30°C experienced reductions in pupation rate, pupal mass, egg load, and adult life span when compared with those reared at lower temperatures. Our analyses of the fate of parasitoids and their hosts and intergenerational population growth at different rearing temperatures show that D. semiclausum and P. xylostella respond differently to temperature, leading to divergent outcomes under different temperature conditions. Some parasitoid larvae could not complete development at 30°C, the temperature at which the host biomass was least and the metabolic demands of the parasitoid could be high, suggesting that parasitoid development might be constrained by lack of host resources at higher temperatures. We discuss the potential mechanisms of parasitoid susceptibility to elevated temperatures, which likely explain the pronounced seasonal dynamics of D. semiclausum in subtropical regions and its failure to establish in lowland tropical regions, where P. xylostella is a serious pest. Similar interactions in other host–parasitoid associations would constrain the efficacy of parasitoids as biological control agents as global temperatures increase. Abstract : Graphical Abstract: Understanding the thermal dynamics of host–parasitoid interactions is crucial to predicting how biological control by parasitoids is affected by climate change. We compared various performance traits of Diadegma semiclausum and its Plutella xylostella host over a wide range of constant temperatures. Parasitoids reared at 30°C experienced reductions in pupation rate, pupal mass, egg load, and adult life span when compared with those reared at lower temperatures. Their underlying mechanisms that we uncovered with multiple methods we newly developed likely explain the pronounced seasonal dynamics of D. semiclausum in subtropical regions and its failure to establish in lowland tropical regions.